Cirrhosis and insulin resistance: current knowledge, pathophysiological mechanisms, complications and potential treatments. Issue 16 (21st August 2020) - Clarembeau, Frédéric; Bale, Georgia; Lanthier, Nicolas
Abstract: End-stage chronic liver diseases are often associated with insulin resistance (IR) and diabetes mellitus (DM). Indeed, to quantify insulin sensitivity the euglycemic clamp technique was utilized, allowing the following to be stated: in small groups of patients, an IR in almost all cirrhotic patients can be observed, compared with a control group. Additionally, it has been demonstrated that IR in cirrhosis is linked to a decreased peripheral (muscle) glucose uptake rather than an increased liver glucose production. The homoeostasis model of IR (HOMA-IR) technique, devised only later, was then exploited to assess this same phenomenon in a larger sample population. The research established that even in patients with preserved liver function, cirrhosis is associated with significant alterations in glucose homoeostasis levels. The purpose of the present paper is to present the current research around the affiliation of cirrhosis and IR, discuss potential mechanisms explaining the association between cirrhosis and IR (i.e. endocrine perturbation, liver inflammation, altered muscle mass and composition, altered gut microbiota and permeability), complications that can arise as well as treatment options, through a critical review of the literature surrounding this subject. This research will also be investigating the beneficial impact, if there is any, of identifying and curing IR in patients with cirrhosis.